National Drug Abuse Treatment System Survey, Waves II-IV - D'Aunno, Thomas ([Verlag nicht ermittelbar], 2009)
The National Drug Abuse Treatment System Survey (NDATSS) is a longitudinal program of research into organizational structures, operating characteristics, and treatment modalities of outpatient drug treatment programs in the United States. This is done through interviews with program directors and clinical supervisors. In some publications, this research is referred to as the Outpatient Drug Abuse Treatment Studies (ODATS). Data being released include Wave II (1988), Wave III (1990), and Wave IV (1995).